The choice of the medicine phosphodiesterase inhibitors of 5th type for treating patients with erectile dysfunction and chronic prostatitis - P. V. Glybochko; Yu. G. Alyaev; Yu. M. Esilevskiy; A. A. Kamalov; Yu. L. Demidko; D. N. Fiev (Сеченовский вестник, 2013)
The study of the genital system' vessels in patients with erectile disfunction and chronic prostatitis was accomplished using ultrasound Dopplerography and pharmacological testing by phosphodiesterase inhibitors of 5th type (PDEI-5). The positive impact of PDEI-5 (such as Sildenafil, Vardenafil, Udenafil and Tadalafil) on organs' blood supply was revealed. The changes of USDG parameters were found comparable and, at the same time, individual. For patient-specific choosing the medicinal agent it is advisable to perform the pharmacological tests for each patient. The choice of the medicine for treating erectile disfunction and chronic prostatitis should be made on the basis of the results of ultrasound Dopplerography and pharmacological testing for each selected and tested medicine. For this purpose it is preferably to choose the medicine, which improves the blood flow in penis and, at the same time, in prostate gland and in testes.